2015
DOI: 10.1007/s11191-015-9757-7
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles to Mathematization in Physics: The Case of the Differential

Abstract: Check the metadata sheet to make sure that the header information, especially author names and the corresponding affiliations are correctly shown. • Check the questions that may have arisen during copy editing and insert your answers/ corrections. • Check that the text is complete and that all figures, tables and their legends are included. Also check the accuracy of special characters, equations, and electronic supplementary material if applicable. If necessary refer to the Edited manuscript. • The publicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
(35 reference statements)
2
13
0
3
Order By: Relevance
“…This fits with the models and frameworks developed by physics education researchers who have argued that using mathematics in physics is quite different to simply using mathematics [26][27][28][29][30]. There are a number of instances in the literature where students demonstrate that they are quite successful manipulating and applying mathematical formulas but struggle to interpret or to generate these formulas [8,12,15,42].…”
Section: A Macroscopic Studies and Findingssupporting
confidence: 70%
“…This fits with the models and frameworks developed by physics education researchers who have argued that using mathematics in physics is quite different to simply using mathematics [26][27][28][29][30]. There are a number of instances in the literature where students demonstrate that they are quite successful manipulating and applying mathematical formulas but struggle to interpret or to generate these formulas [8,12,15,42].…”
Section: A Macroscopic Studies and Findingssupporting
confidence: 70%
“…It may also negatively impact the students' fluency to combine the individual equations and simplify the resulting equation for the required variable. Previous studies have reported that students struggle with transferring and using their mathematical knowledge and skills in the physics context [1,24,25,28]. In our case, as mathematical complexity increases, the students may find it even more difficult to apply their mathematical knowledge in the physics domain.…”
Section: Mathematical Complexity and Its Influence On Student Mathmentioning
confidence: 62%
“…Respecto a la dimensión epistémica, autores como Artigue, Menigoux y Viennot (1990), Bos (1974), Kleiner (2012), López-Gay (2001), Pulido (1997), Tall (1981a), Taylor (1974) y Valdivé y Garbin (2008) analizan la evolución histórica del concepto de diferencial y su estrecha relación con nociones como cantidad infinitamente pequeña, infinitesimal, aproximación lineal, aproximación o estimación lineal del incremento, destacando sus implicaciones en los procesos de enseñanza y aprendizaje. Gómez (2019), Martínez-Torregrosa et al (2002) y López-Gay et al (2015) plantean que una de las dificultades de tipo cognitivo se produce por la diversidad de significados que se les presenta a los estudiantes, ya que hay que tener en cuenta las diferentes definiciones que se fueron presentando a lo largo del desarrollo del cálculo y su articulación con las diversas representaciones y contextos.…”
Section: Introductionunclassified